Methylene Blue Use in Pediatrics - Moss, Rachel; Derespina, Kim R.; Frye, Jessica; Kaushik, Shubhi (Journal of Pediatric Intensive Care, 2023)
Catecholamine-resistant shock, also known as vasoplegia, is a challenging entity with a significant risk of mortality. We seek to provide further data on the safety and effectiveness of methylene blue (MB) for vasoplegic shock in the pediatric population. We conducted a retrospective observational study of pediatric patients admitted to the pediatric intensive care unit or pediatric cardiac intensive care unit at Mount Sinai Kravis Children's Hospital from 2011 to 2021 who received MB for refractory shock. A list of patients was obtained by performing a pharmaceutical query from 2011 to 2021 for “MB.” Chart review was performed to determine indication for use and to collect demographic and clinical data. There were 33 MB administrations: 18 administrations (16 unique patients) for vasoplegic shock, 11 for surgical dye, and 4 for methemoglobinemia. The median age was 5 years (interquartile range [IQR]: 0.08, 13). Ten patients required MB following congenital cardiac repair (62.5%); one administration for myocarditis, septic shock, postcardiac arrest, high output chylothorax, scoliosis repair, and one multisystem inflammatory syndrome in children. No patients experienced hemolytic anemia or serotonin syndrome following administration. The median dose of MB was 1 mg/kg. Vasoactive-inotrope score (VIS) improved in 4 out of 18 administrations at 1 hour. Mean arterial pressure (MAP) improved in 10 out of 18 administrations at 1 hour. Systolic blood pressure (SBP) improved in 8 out of 18 administrations at 1 hour. VIS, MAP, and SBP improved in 8 out of 18 administrations at 6 hours. MB may be safely considered as rescue therapy in catecholamine-resistant shock in pediatrics.
Keywords: vasoplegic shock; methylene blue; vasoplegia; pediatrics